Role of pectoral nerve block (PECS II) in post-operative pain management for breast surgeries - Mili Yadav; Amey Dixit; Arvind Kumar Rathiya; Subhash Kumar Agrawal (Asian Journal of Medical Sciences, 2022)
Background: Pain after breast surgeries is a major problem which costs both in patient comfort and duration of hospital stay. Uncontrolled post-operative pain may produce a range of detrimental acute and chronic effects. Optimal pain relief and minimal side effects following surgery have a major impact on patient outcome, including patient satisfaction and earlier mobilization, as well as fulfilling the needs for streamlined surgical services with lower costs.